Evaluation of SF6 Leakage from Gas Insulated Equipment on Electricity Networks in Great Britain - Phillip Widger; Abderrahmane (Manu) Haddad (Energies, 2018)
This paper examines the data collected from the power industry over the last six years of actual reported emissions of sulphur hexafluoride (SF6) and the potential impact. The SF6 emissions have been collated from the 14 different regions in England, Scotland, and Wales (Great Britain) from the six distribution network operators. The emissions of SF6 due to the transmission network of Great Britain have also been collated from the three different transmission network operators. By collecting this SF6 emissions data from the power industry, in both the distribution and transmission networks, an overall view of the scale of SF6 emissions in Great Britain can be evaluated. Data from the power industry also shows the inventory of SF6 power equipment in use over the last six years in Great Britain and shows the calculated percentage leakage rate of all of this equipment. In this paper, these figures, as reported by the electrical power industry to the UK government, have been used to estimate the likely inventory of SF6 equipment in England, Scotland, and Wales by 2050 and the future emissions of SF6 that could be leaked into the atmosphere by this equipment.